Sudden Bilateral Sensorineural Hearing Loss Associated with HLA A1-B8-DR3 Haplotype. (9th September 2013) - Psillas, G.; Daniilidis, M.; Gerofotis, A.; Veros, K.; Vasilaki, A.; Vital, I.; Markou, K.
Abstract : Sudden sensorineural hearing loss may be present as a symptom in systemic autoimmune diseases or may occur as a primary disorder without another organ involvement (autoimmune inner ear disease). The diagnosis of autoimmune inner ear disease is still predicated on clinical features, and to date specific diagnostic tests are not available. We report a case of bilateral sudden hearing loss, tinnitus, intense rotatory vertigo, and nausea in a female patient in which the clinical manifestations, in addition to raised levels of circulating immune complexes, antithyroglobulin antibodies, and the presence of the HLA A1-B8-DR3 haplotype, allowed us to hypothesize an autoimmune inner ear disease. Cyclosporine-A immunosuppressive treatment in addition to steroids helped in hearing recovery that occurred progressively with normalization of the hearing function after a five-month treatment. Cyclosporine-A could be proposed as a therapeutic option in case of autoimmune inner ear disease allowing the suspension of corticosteroids that, at high dose, expose patients to potentially serious adverse events.